2021
DOI: 10.3390/healthcare9040434
|View full text |Cite
|
Sign up to set email alerts
|

Self-Care in Heart Failure Inpatients: What Is the Role of Gender and Pathophysiological Characteristics? A Cross-Sectional Multicentre Study

Abstract: Heart failure is often characterised by low exercise capacity and a great impairment of performance in the activities of daily living. The correct management of the disease can prevent the worsening of symptoms and promote a better quality of life. The aims of this study are to understand the relationship of gender and pathophysiological characteristics with self-care behaviour and to evaluate the self-care behaviour in a sample of Portuguese heart failure inpatients, using the Self-Care of Heart Failure Index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…23 Several studies showed that gender was not the predictor of selfcare management in HF patients. 20,24 Meanwhile, it affected the outcome as suggested in a previous study which stated that there are different outcomes between men and women based on mortality and rehospitalization after practicing self-care management. 8 This indicated that self-care needs to be implemented based on gender differences to improve patients' prognoses.…”
Section: Significance For Public Healthmentioning
confidence: 96%
“…23 Several studies showed that gender was not the predictor of selfcare management in HF patients. 20,24 Meanwhile, it affected the outcome as suggested in a previous study which stated that there are different outcomes between men and women based on mortality and rehospitalization after practicing self-care management. 8 This indicated that self-care needs to be implemented based on gender differences to improve patients' prognoses.…”
Section: Significance For Public Healthmentioning
confidence: 96%
“…Manajemen perawatan diri dapat ditingkatkan dengan edukasi dan pelatihan melalui simulasi (Jaarsma et al, 2017;Trojahn et al, 2013). Melakukan edukasi dan pelatihan yang mendukung untuk meningkatkan perilaku perawatan mandiri pada pasien gagal jantung dapat meningkatkan pengetahuan, keterampilan, menurunkan gejala, dan mengurangi keluhan penderita (Delgado et al, 2021;Dewi et al, 2019;Riegel et al, 2009;Salahodinkolah et al, 2019).…”
Section: Pendahuluanunclassified
“…Studies on single chronic diseases have shown conflicting results regarding the influence that patient and caregiver sex can have on patient self-care. Some studies conducted on heart failure (HF) (Dellafiore, Arrigoni, et al, 2018), diabetes mellitus (DM) (Ausili et al, 2018), hypertension (Salim et al, 2019), and people with an ostomy (Giordano et al, 2021) found that male patients performed lower self-care behaviors than females whereas other studies report no differences in self-care between male and female patients with HF (Delgado et al, 2021), and others report that females with DM performed lower self-care than males (McCollum et al, 2005).…”
Section: Introductionmentioning
confidence: 99%